2016
DOI: 10.1021/acs.bioconjchem.6b00403
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselectivity of 5-Methyluridine Osmylation Is Inverted inside an RNA Chain

Abstract: In this study, we investigated the reaction of the osmium tetroxide-bipyridine complex with pyrimidines in RNA. This reagent, which reacts with the diastereotopic 5-6 double bond, thus leading to the formation of two diastereomers, was used in the past to label thymidine and 5-methylcytosine in DNA. In light of the growing interest in post-transcriptional RNA modifications, we addressed the question of whether this reagent could be used for labeling of the naturally occurring RNA modifications 5-methylcytosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Furthermore, we note that there is no indication for oxidation of the 5,6‐double bond of pyrimidines under the conditions used. This could however become a potential side reaction if higher concentrations of OsO 4 and additives, such as pyridines or bipyridines, were applied that stabilize the pyrimidine OsO 4 adducts …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we note that there is no indication for oxidation of the 5,6‐double bond of pyrimidines under the conditions used. This could however become a potential side reaction if higher concentrations of OsO 4 and additives, such as pyridines or bipyridines, were applied that stabilize the pyrimidine OsO 4 adducts …”
Section: Resultsmentioning
confidence: 99%
“…OsBp addition to the pyrimidine C5-C6 double bond occurs from either the top or from the bottom of the pyrimidine ring yielding two topoisomers. 40,41,52 Due to the strand directionality these two isomers are detectable by either HPLC or CE (see profiles of osmylated 31nt oligos in Supplementary Information, part C). Two peaks were observed for every singly osmylated oligo tested here with a product ratio not far from unity, so that both are detectable.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike in the case of short RNA strands, HPLC traces that originated from osmium complex formation were negligible if m 5 C was incorporated into the inside of a 10‐nt single‐stranded (ss) RNA sequence AA(m 5 C)AAGAUCU. Previous studies performed by Tserovski and Helm showed that the reaction rate of m 5 C towards osmium oxidation was low and decreased significantly with an increase in the size of the RNA chain . Therefore, an indirect approach, specifically, enzymatic digestion of the target RNA prior to osmium oxidation, was considered.…”
Section: Methodsmentioning
confidence: 99%